The opossum and other didelphids in the cultures of Costa Rican society and indigenous peoples: an approach to ecology and conservation - Azofeifa Romero, Yara (2024)
The opossum Didelphis marsupialis, commonly referred to as the zorro pelón in Costa Rica, is a marsupial that holds significant representation in both Costa Rican and indigenous cultures, such as the Talamanca natives. This species, along with the other ten opossums found in Costa Rica, constitute one of the groups of mammals with the least representation in scientific literature. This study aims to (1) document the knowledge, uses, perceptions, and human-zorro pelón interactions through surveys conducted with individuals in three types of zones: rural, semi-urban, and urban; and (2) explore the presence of opossums in the 19th-century worldview of farmers and in the cosmovision of indigenous peoples. We performed an analysis on the text and Likert-scale data collected from 296 surveys conducted across seven provinces in Costa Rica. Nonparametric tests were conducted to assess whether the type of zone influenced the interactions and perceptions of individuals. Valuable information was obtained from key participants and informants regarding the behavior, observation sites, diet, and population trends of the species. The remarkable adaptability of the zorro pelón is evident in rural and semi-urban environments, but not in urban zones. The human-zorro pelón interaction data between the rural and semi-urban zones are similar, but these differ significantly from the urban zone. Although people surveyed generally have a positive perception of the opossum, there has been a notable devaluation over time when compared to the imaginary of indigenous cultures. Parallels were observed in the beliefs and uses of marsupials between pre-Columbian societies and contemporary Costa Rican societies. As part of the educational strategies for the conservation of marsupials, it is important to promote their appreciation and refute negative stereotypes, such as by informing about their ecological role and their ability to resist pathogens and venom. In this context, the rich symbolism of the opossum can be utilized to adapt the message to the various regions of America.